Two sides of the same coin: heat shock proteins as biomarkers and therapeutic targets for some complex diseases - Makhoba, Xolani Henry (Frontiers in Molecular Biosciences, 2025)
Heat shock proteins are molecular chaperones that play crucial roles in the folding and unfolding of complex polypeptides within the cellular system. These molecules are involved in various processes, including vesicular transport, prevention of protein aggregation in the cytosol, and cell signaling. They are also linked to autoimmunity, infection immunity, and tumor immunology. Stressors like heat shock, exposure to heavy metals, cytokines, reactive oxygen species, inflammation, and viruses can influence the production of these molecules. In complex diseases such as cancer, malaria, and COVID-19, heat shock proteins are considered both biomarkers and drug targets. The upregulation of small heat shock proteins like hsp27 and major heat shock proteins 70/90 has been recognized as crucial biomarkers and therapeutic targets for cancer. Additionally, it has been reported that the invasion of Plasmodium falciparum, the causative agent of malaria, leads to the upregulation of heat shock proteins such as hsp40, hsp70, and hsp90. This sudden increase is a protective mechanism from the human host and enhances the parasite’s growth, making these proteins significant as biomarkers and malarial drug targets. The presence of the SARS-CoV-2 virus in the human cellular system correlates with a substantial increase in heat shock protein 70 production from host cells. Furthermore, our research group has demonstrated that SARS-CoV-2 hijacks the host’s heat shock proteins, and we are currently developing tools to prevent the virus from utilizing the host’s protein folding system. This review aims to highlight the role of heat shock proteins as biomarkers and therapeutic targets for selected refractory diseases, focusing on cancer, malaria, and COVID-19. A fundamental molecular docking study was performed to investigate the interaction between a non-structural complex from SARS-CoV-2 and chosen small molecules, which is emphasized in this review.